The Effects of a Web-Based Need-Supportive Intervention for Physical Education Teachers on Students’ Physical Activity and Related Outcomes: A Randomized Controlled Trial - Hasso Paap; Andre Koka; Pille-Riin Meerits; Henri Tilga (Children)
Background/Objectives: Globally, adolescents are insufficiently active, highlighting the need for effective strategies to enhance their activity levels. This study evaluated a web-based intervention program designed for physical education (PE) teachers, aimed at fostering students’ basic psychological needs—autonomy, competence, and relatedness—in PE settings. Methods: Secondary school PE teachers and their students were randomly assigned into either an experimental (teachers n = 36; students n = 463, Mage = 13.94, SD = 0.88) or a control group (teachers n = 49; students n = 820, Mage = 13.93, SD = 0.87). Teachers in the experimental group underwent a 4-week web-based intervention program focused on autonomy-, competence-, and relatedness-supportive motivational techniques. Students completed questionnaires assessing psychological measures and self-reported physical activity (PA) before and after the teachers’ training. Results: Results indicated that students in the experimental group perceived significantly higher autonomy, competence, and relatedness support compared to their control group counterparts at post-test. Conclusions: Consequently, the web-based need-supportive intervention was effective in promoting need-supportive teacher behavior. As the developed training for PE teachers increased students’ perceptions of need support from their PE teachers, it holds promise for future PE teacher education. Furthermore, the web-based format offers scalability for broader implementation.